Exportaciones manufactureras y productividad laboral de los países de América Latina durante el período 2000-2018 - Luisa Estefania, Flores Padilla (2021)
ABSTRACT This research analyzes the behavior of manufacturing exports and labor productivity in 6 Latin American countries during the period 2000-2018. The empirical evidence raised and Kaldor's theory about the possible causal relationship between the variables will be taken into account to perform an analysis on the study variables. A primary method is proposed for panel data by ordinary least squares, control variables such as real exchange rate and gross fixed capital formation are added. The first result is that labor productivity has a positive and significant effect on manufacturing exports; however, the control variables show a non-significant positive effect at 10%. Subsequently, an analysis of the variance is carried out, and it can be seen that the variable with the most significant impact in the coming years will be manufacturing exports. Keywords: Kaldor theory, panel data, manufacturing exports, labor productivity, variance Reviewed by: Mgs: Sonia Granizo Lara. ENGLISH PROFESSOR. C.C. 0602088890